Children's stationeries and the innovation design and development of DIY KiDZSTATiON / Zatul Himmah Abdul Karim ... [et al.] - Abdul Karim, Zatul Himmah; Anual, Norazlan; Nik Hassan, Nik Suriati; Mat Halif, Mazuin; Mohd Hassan, Norsilawati (2021)
Stationeries are one of the most important tools needed by school children to facilitate their learning process. Often, parents of children in the age group of 4 - 12 years are known to purchase stationeries and this behaviour has reached to an extent that the cost of buying these Stationeries has surpassed other basic needs. The loss of stationeries among school children frequently happened due to the child's carelessness, stolen or misplaced. The purpose of this research was to determine the exact cost parents will have to bear for their child's stationeries and to determine the most effective way to minimize missing stationeries by having an intact product that keeps all stationeries safe. The paper also intends to introduce the development of a DIY product called KiDZSTATiON. Questionnaire was developed and distributed using online survey. Convenience sampling was adopted, and data was collected using Google form. 120 respondents answered the questionnaire using their mobile phones. This study was based on the findings of a small sample of potential users. It was found that majority of the parents reported having serious issues with their children missing Stationeries at school with 52% agreed that the repurchasing of stationeries affected their money spending. In the meantime, this paper also reports the process of an innovative transformation from current stationeries and other available and cheap resources to KiDZSTATiON. A design-based research framework with four phases steps were used in designing and developing this do-ityourself (DIY) innovation. It was also found that an overwhelming 84% of the respondents thought that KiDZSTATiON would significantly help parents to keep children's stationeries intact, and eventually help to eliminate extra purchases on unnecessary buying of their children's stationeries. It is recommended that parents with young children should have at least one set of KiDSTATIiON for each child.